xidative Stabilization of Sacha Inchi [Plukenetia Volubilis Linneo] Oil with Mortiño [Vaccinium Meridionale SW] Suspensions Addition. - Zapata Acosta, K.; Piedrahita, A. M.; Alzate, A. F.; Cortés, F. B.; Rojano, B. A. (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Sacha inchi (Plukenetia volubilis Linneo) oil has been recognized worldwide for its high Omega content.However, the presence of polyunsaturated fatty acids make the oil substantially susceptible to oxidativedeterioration. In this study, the eect of mortiño (Vaccinium meridionale SW) suspensions at 1000, 1500 and 2000 mg L-1 on the oxidative stability of Sacha inchi (Plukenetia volubilis Linneo),oil under accelerated oxidation conditions for 12 hours (60 °Cand 1700 mL.min-1 air flow) was evaluated. The extent of oxidative damage was monitored by measuring the formation of polar compounds (CP), conjugated trienes (TC) and peroxide value (PV) of the oil in the presence and absence of the suspension. The results revealed that the additive is eective in stabilizing Sacha inchi (Plukenetia volubilis Linneo) oil, so that concentrations of 2000 mg L